Speech or silence: The effect of user anonymity and member familiarity on the willingness to express opinions in virtual communities. Issue 7 (4th November 2014) - Luarn, Pin; Hsieh, Ai-Yun
Abstract : Purpose: – The purpose of this paper is to extend a traditional communication theory, spiral of silence, to explore the effects of user anonymity and member familiarity on opinion expression behaviour in a virtual environment. Design/methodology/approach: – A laboratory experiment method was used to manipulate user anonymity, member familiarity, and opinion congruity to measure the willingness to express opinions concerning controversial topics. Findings: – A total of 147 participants were recruited in the experiment. The results revealed that anonymous users in virtual communities and users in groups comprising familiar members are more willing to express inconsistent opinions than non-anonymous users and users in groups containing unfamiliar members, respectively. In addition, anonymous and non-anonymous users as well as users in groups comprising familiar members and those in groups containing unfamiliar members are equally willing to express consistent opinions. Originality/value: – This is the first study to verify the effect of user anonymity and member familiarity on the willingness to express opinions in online social communities. The findings have crucial implications regarding how governments and businesses can stimulate creativity and feedback through virtual communities.